“A weekend with Pablo Escobar”: the narrative exercise of an author - Alzate Vargas, César (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
Twenty years after the publication of one of the most famous chronicles of recent Colombia, this article analyzes the always latent relationship between journalistic and literary writing, delving into the details that make a text like Juan José Hoyos’s a piece of which it can be said without ambiguity that it is literature. In order to carry out the analysis, we resort to the proposals that the author of the chronicle himself, in addition to writers such as Daniel Samper Pizano, make to understand the journalism-literature relationship.